GAMBARAN STATUS GIZI IBU HAMIL TRIMESTER I - Mulyana, Ririh Setya; Widyasih, Hesty; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2015)
The chronic energy deficiency is one of the main nutritional problems in Indonesia. Data from Riskesdas in 2013 that the prevalence of chronic energy deficiency in Indonedia is 24.4%. Data from Health Departement in DIY province states that the prevalence of chronic energy deficiency of pregnant women at he age of 15-49 years old is 11.2%. the highest prevalence in Yogyakarta 18.1%. Puskesmas Gondokusuman II more over than in Puskesmas Gondokusuman I. The numberf of it is 18.1%. The research describes that the nutritional status of pregnant women in first trimester based on aged, parity, anemia status, the prohibition food, and dietary habit. The kind of the research id descriptive with cross-sectional design. the research was done at March-May in 2015. The location of research is in Puskesmas Gondokusuman I dan II Yogyakarta. The subject of research is 47 pregnant women. The most nutritional status of pregnant women at the first trimester in Puskesmas Gondokusuman I and II is not at the risk. The chronic energy deficiency is 92,6% and 80%. Based of the factors of age, parity, anemia status, prohibition food, and dietary habit most of the pregnant women is not at risk. The conclusion is most of the pregnant women at the first trimester is not risk of chronic energy deficiency.